Macro and micro level impulse responses: A survey experimental identification procedure - Dirk Drechsel; Heiner Mikosch; Samad Sarferaz; Matthias Bannert (ETH Zurich, KOF Swiss Economic Institute, 2015)
This paper analyzes the effects of macroeconomic shocks on prices and output at different levels of aggregation using a bottom up approach. We show how to generate firm level impulse responses by incorporating experimental settings into surveys and by exposing firm executives to treatment scenarios. Aggregation then results in industry level and economy wide impulse responses. We further show that the effects obtained from survey experiments can be mapped into impulse responses retrieved from VARs. We apply the procedure to study the effects of oil price shocks using a representative sample of over 1000 Swiss firms. At the aggregate and industry level our findings confirm, with some notable exceptions, results from a standard VAR. At the micro level we analyze the driving forces behind firm specific impulse responses, controlling for several firm characteristics via panel data analysis and thereby solving existing puzzles.
Keywords: C32; C83; C99; E31; 330; Survey based impulse responses; survey experiments; macroeconomic shock identification; firm level data; oil price shock